Permanent pacing post-Fontan is not associated with reduced long-term survival. (11th December 2019) - Hall, Sally J.; Cullington, Damien; Thomson, John D. R.; Bentham, James R.
Abstract: Background: The Fontan procedure is the final stage of surgical palliation for a single-ventricle circulation. Significant complications are common including rhythm disturbance necessitating implantation of a permanent pacemaker. This has been widely considered a negative prognostic indicator. Methods: This single-centre, retrospective case control study involved all patients who underwent the Fontan procedure at the Leeds Congenital Heart Unit between 1990 and 2015 and have had regular follow-up in Yorkshire and Humber, United Kingdom. 167 Fontan patients were identified of which 2 were excluded for having a pre-procedure pacemaker. Of the remainder, 23 patients required a pacemaker. Outcomes were survival, early and late complications, need for further intervention and oxygen saturation in long-term follow-up. Results: There was no difference in survival (30-day survival pacemaker 92.6%, sinus rhythm 90.5%, p = 0.66, 1-year pacemaker 11.1%, sinus rhythm 10.1%, p = 1). The pacemaker group was more likely to have cerebral or renal complications in the first-year post-procedure (acute kidney injury: sinus rhythm 0.8%, pacemaker 19.1%, p = 0.002). No difference was observed in longer term complications including protein losing enteropathy (sinus rhythm 3.5%, pacemaker 0% p = 1). There was no difference in saturations between the two groups at follow-up. Paced patients were more likely to have required further intervention, with a higher incidence of cardiopulmonary bypass procedures (sinus rhythm 6.3%, pacemaker 35%, p < 0.001). Conclusions: Despite an increase in early complications and the need for further interventions, pacemaker requirement does not appear to affect long-term survival following the Fontan procedure.